East–West cooperation in the automotive industry: Enterprises, mobility, production. Issue 1 (June 2017) - Fava, Valentina; Gatejel, Luminita
The paper introduces the special issue 'East–West cooperation in the automotive industry: Enterprises, mobility, production' which includes four contributions on the development of socialist automotive industry and on the technological relations between Eastern and Western Europe during the Cold War. The 1960s and 1970s intense relations between socialist governments and Western European automobile companies provide further evidence of the permeability of the Iron Curtain, the early entanglements between the two blocs and the lack of internal cohesion inside each of them. The papers stress the role of the enterprise, both socialist and capitalist, as a crucial agent in directing East–West flows of technology and knowledge. They invite to reconsider the classical vision of West–East transfer of technology and to go deeper in the study of the political uses of foreign technology and on the processes of reception, adaptation and transformation of Western technologies in Socialist Europe.